Evaluation of Midwifery Students in Labor and Delivery Training: Comparing two Methods of Logbook and Checklist - nazal Ajh (مجله ایرانی آموزش در علوم پزشکی, 2006)
Introduction: Different evaluation methods have been introduced for evaluating clinical skills. Using checklist and logbook are common methods in clinical units. The purpose of this study was to compare logbook and checklist as the means for evaluating midwifery students in labor and delivery training. Methods: This pre-experimental study was performed in Hazrat Zaynab Nursing and Midwifery School affiliated to Gilan University of Medical Sciences in the first semester of 2005. The study sample included all midwifery senior students (n=21). In order to record students’ daily scores, the students and their instructors were provided with a logbook including all the skills they were supposed to acquire. The instructors checked all students’ activities using a checklist at the end of semester, while at the same time, the instructors and students had to evaluate and mark any daily activity, using the logbook. The data was analyzed by SPSS software using frequency distribution, mean, standard deviation and t-test. Results: The mean and standard deviation of the scores recorded using the logbook and checklist were 16.33±.77 and 17.88±.41, respectively, which had a significant difference. At the beginning, all students were completely satisfied with the new method of evaluation, but after receiving the results, their satisfaction rate decreased to 85.71%. The students had significantly more satisfaction with logbook. Conclusion: Using logbook provided a more objective evaluation and led to more students’ satisfaction. However, using logbook requires more studies and revisions in other university centers.